Vertical Craniofacial Morphology and its Relation to Temporomandibular Disorders - Paula Furlan Bavia; Renata Cunha Matheus Rodrigues Garcia (Stilus Optimus, 2016)
Objectives: This study investigated the association between craniofacial morphology and temporomandibular disorders in adults. The influence of different craniofacial morphologies on painful temporomandibular disorders was also evaluated. Material and Methods: A total of 200 subjects were selected, including 100 with temporomandibular disorders (TMD) and 100 without TMD (control), diagnosed by research diagnostic criteria for temporomandibular disorders. All subjects were submitted to lateral cephalometric radiographs, and classified as brachyfacial, mesofacial, or dolichofacial by Ricketts' analysis. Data were analysed by Tukey-Kramer and Chi-square tests. Results: No association between craniofacial morphology and TMD was found (P = 0.6622). However, brachyfacial morphology influences the presence of painful TMD (P = 0.0077). Conclusions: Craniofacial morphology is not related to temporomandibular disorders in general.